Registration and Management of "Never Events" in Swiss Hospitals—The Perspective of Clinical Risk Managers. Issue 8 (25th December 2021) - Schwappach, David L. B.; Pfeiffer, Yvonne
Abstract : Background: In Switzerland, there is no mandatory reporting of "never events." Little is known about how hospitals in countries with no "never event" policies deal with these incidents in terms of registration and analyses. Objective: The aim of our study was to explore how hospitals outside mandatory "never event" regulations identify, register, and manage "never events" and whether practices are associated with hospital size. Methods: Cross-sectional survey data were collected from risk managers of Swiss acute care hospitals. Results: Clinical risk managers representing 95 hospitals completed the survey (55% response rate). Among responding risk and quality managers, only 45% would be formally notified through a designated reporting channel if a "never event" has happened in their hospital. Averaged over a list of 8 specified events, only half of hospitals could report a systematic count of the number of events. Hospital size was not associated with "never event" management. Respondents reported that their hospital pays "too little attention" to the recording (46%), the analysis (34%), and the prevention (40%) of "never events." All respondents rated the systematic registration and analysis of "never events" as very (81%) or rather important (19%) for the improvement of patient safety. Conclusions: A substantial fraction of Swiss hospitals do not have valid data on the occurrence of "never events" available and do not have reliable processes installed for the registration and exam of these events. Surprisingly, larger hospitals do not seem to be better prepared for "never events" management.